The Effect of Location, Price, and Menu Variants on Repurchase Intention with Emotional Attachment as a Mediating Variable at the Viral Mobile Coffee in Jl. Pahlawan, Semarang - Alkautsar, Alif; Ratnawati, Alifah (Majapahit Journal of Islamic Finance and Management, 2025)
Ajzen, I. (1991). The theory of planned behavior. Organizational Behavior and Human Decision Processes. Organizational Behavior and Human Decision Processes, 50(2), 179–211. Amalia, N. R., & Saryadi, S. (2018). PENGARUH KEMUDAHAN AKSES DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS ONLINE TIKET.COM. Jurnal Ilmu Administrasi Bisnis, 7(3), 404–414. https://doi.org/10.14710/jiab.2018.21057 Anisa, D. (2023). Inilah 5 Daerah Penghasil Kopi Terbesar di Jawa Tengah. PT. Aksara Solopos. https://regional.espos.id/inilah-5-daerah-penghasil-kopi-terbesar-di-jawa-tengah-1651804 Aulia, A. P., Arum, R. M., & Hardiyansyah, H. (2024). THE INFLUENCE OF EASE OF USE, TRUST AND E-SERVICE QUALITY ON REPURCHASE INTENTION OF CARE & BEAUTY PRODUCT IN E-COMMERCE WITH E-SATISFACTION AS AN INTERVENING VARIABLE. ICCD, 6(1), 275–282. https://doi.org/10.33068/iccd.v6i1.772 Ferdinand, A. T. (2000). ManajemenPemasaran: Sebuah Pendekatan Strategik. Universitasi Diponogoro. Ghorbanzadeh, D., & Rahehagh, A. (2020). The role of emotional structures in the relationship between satisfaction and brand loyalty. Cogent Psychology, 7(1). https://doi.org/10.1080/23311908.2020.1782098 Ghozali, I. (2008). Structural equation modeling: Teori, konsep, dan aplikasi dengan Program Lisrel 8.80. Badan Penerbit Universitas Diponegoro. Irawan, D., Benardi, B., & Hanifah, H. (2025). Peran Artificial Intelegence (AI) dalam Mempersonalisasi Pengalaman Pelanggan. Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 4(1), 134–140. Keller, K. L. (2003). Strategic Brand Management: Building, Measuring, and Managing Brand Equity. Pearson Education. Kotler, P. (2020). Marketing Management. P. Ed Custom Books. Kotler, P., & Armstrong, G. (2018). Principles of Marketing (17th ed.). The University of Minnesota Libraries Publishing. https://www.amazon.com/Principles-Marketing-17th-Gary-Armstrong/dp/9352865618 Kotler, P., & Armstrong, G. M. (2012). Principles of Marketing. Pearson Prentice Hall. Kotler, P., Keller, K. L., & Chernev, A. (2021). Marketing Management. Pearson Education. Mayora, S. (2022). Pengaruh Kualitas Pelayanan Dan Gaya Hidup Terhadap Keputusan Pembelian Pada Cafe Gerobak Di Payakumbuh. Universitas Islam Riau. Ozdemir, B., & Caliskan, O. (2015). Menu design: A review of literature. Journal of Foodservice Business Research, 18(3), 189–206. Putri, E. H. L., Sulhaini, S., & Mulyono, L. E. H. (2023). Pengaruh Brand Experience, Cita Rasa, Dan Variasi Menu Terhadap Minat Beli Ulang Di Kedai Serabi Bandung. JMM UNRAM-MASTER OF MANAGEMENT JOURNAL, 12(3), 319–331. Putri, O. M., Azmiyah, U., & Muzdalifah, L. (2023). Pengaruh Store Atmosphere Terhadap Niat Beli Konsumenmelalui Positive Emosion Sebagai Variabel Mediasi Di Cafemerci Sidoarjo. Journal of Student Research, 1(1), 356–371. Ramadhany, N. A., & Suyatno, M. (2025). Pengaruh Lokasi, Persepsi Harga, Dan Variasi Menu Terhadap Kepuasan Konsumen Pada Kedai Jinawi Di Menanggal Surabaya. TOMAN: Jurnal Topik Manajemen, 2(1), 113–128. Sabu, S. (2024). Tren Kopi Gerobak Meningkat, Bersaing dengan Coffee Shop. iNews Manado website. https://manado.inews.id/read/ 497110/tren-kopi-gerobak-meningkat-bersaing-dengan-coffee-shop/all Safira, B. (2023). Strategi Pengembangan Bisnis Gerai Kopi pada Tanatap Artisan, Meruya, Kota Jakarta Barat. UIN Syarif HIdayatullah Jakarta. Santika, E. F. (2024). Proyeksi Volume Produksi, Net Ekspor, dan Konsumsi Kopi Indonesia (2022-2026). databoks.katadata.co.id. https://databoks.katadata.co.id/agroindustri/statistik/a927a4885a13422/ini-gambaran-produksi-ekspor-konsumsi-kopi-indonesia-hingga-2026 Schiffman, L. G., & Kanuk. (2012). Consumer Behaviour. New Jersey: Prentice Hall. Singgih, A. C. N., Lengkong, V. P. K., & Lumanauw, B. (2024). Pengaruh Keragaman Menu dan Potongan Harga terhadap terhadap Keterikatan Merek pada Starbucks Manado Town Square. Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis Dan Akuntansi, 12(03), 646–658. https://doi.org/10.35794/emba.v12i03.57530 Sinurat, A. A., Simanjorang, E. F. S., & Zebua, Y. (2024). The Influence of Product Price, Outlet Location, and Discounts on the Interest to Rebuy. Almana : Jurnal Manajemen Dan Bisnis, 8(1), 29–38. https://doi.org/10.36555/almana.v8i1.2314 Sugiyono, P. (2015). Metode penelitian kombinasi (mixed methods). Bandung: Alfabeta, 28(1), 12. Thomson, M., MacInnis, D. . J., & Park, C. W. (2005). Les liens attachants: Mesurer la force de l’attachement émotionnel des consommateurs à la marque. Recherche et Applications En Marketing (French Edition), 20(1), 79–88. Tyas, D. W., Kusumaningrum, H., Kusumawati, P., & Wiratma, H. D. (2023). STRATEGI BISNIS ANGKRINGAN KOPI JOSS SEBAGAI PENDUKUNG PARIWISATA KOTA YOGYAKARTA SELAMA PANDEMI COVID-19. Kepariwisataan: Jurnal Ilmiah, 17(1), 47–62. https://doi.org/10.47256/kji.v17i1.202 Utari, T., & Pasaribu. (2024). PENGARUH SERVICESCAPE DAN HARGA TERHADAP KEPUASAN EMOSIONAL PELANGGAN DI KEDAI CISANGKUY PADANG. Jurnal Manajemen Perhotelan Dan Pariwisata, 7(2), 150–157. https://doi.org/10.23887/jmpp.v7i2.84064 Wahyuningsih, S., Wibowo, H., Hastuti, D., & Wilantika, D. (2022). ANALYSIS OF COFFEE EXPORT COMPETITIVENESS IN CENTRAL JAVA PROVINCE 2014-2019. MEDIAGRO, 18(2). Mediagro, 18(12). Wulanjani, H., & Derriawan, D. (2017). Dampak utilitarian value dan experiential marketing terhadap customer satisfaction dan revisit intention. Jurnal Riset Manajemen Dan Bisnis, 2(2). Zeithaml, V. A., Berry, L. L., & Parasuraman, A. (1996). The Behavioral Consequences of Service Quality.